Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/4973878
|View full text |Cite
|
Sign up to set email alerts
|

Prone versus Supine Position Ventilation in Adult Patients with Acute Respiratory Distress Syndrome: A Meta-Analysis of Randomized Controlled Trials

Abstract: The purpose of this meta-analysis was to compare the efficacy and safety of prone versus supine position ventilation for adult acute respiratory distress syndrome (ARDS) patients. The electronic databases of PubMed, Embase, and the Cochrane Library were systematically searched from their inception up to September 2020. The relative risks (RRs) and weighted mean differences (WMDs) with corresponding 95% confidence intervals (CIs) were employed to calculate pooled outcomes using the random-effects models. Twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Prone positioning is common practice in mechanically ventilated patients suffering from acute hypoxaemic respiratory failure or acute respiratory distress syndrome [ 11 , 25 , 26 ]. This study looked at the effect of proning cycles on oxygenation (∆PaO 2 /FiO 2 or P/F ratio) in mechanically ventilated COVID-19 patients after each proning episode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prone positioning is common practice in mechanically ventilated patients suffering from acute hypoxaemic respiratory failure or acute respiratory distress syndrome [ 11 , 25 , 26 ]. This study looked at the effect of proning cycles on oxygenation (∆PaO 2 /FiO 2 or P/F ratio) in mechanically ventilated COVID-19 patients after each proning episode.…”
Section: Discussionmentioning
confidence: 99%
“…The seminal randomized controlled trial of severe ARDS patients demonstrated that 16 h of proning improved survival, which has been supported by subsequent meta-analyses [ 11 , 12 ]. However, in most ARDS studies, the total duration of prone positioning was <7 days [ 11 , 12 , 26 ], and the clinical efficacy of the prone position after seven days in mechanically ventilated COVID-19 patients remains unclear. We continued to perform proning cycles until the patient was clinically improved and no longer required a FiO 2 of 0.6 or above to maintain a PaO 2 of 60 mmHg (i.e., a PaO 2 /FiO 2 of >100 mmHg) and observed an on-going benefit with this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, APP is safe. Previous studies have shown that a PP combined with invasive mechanical ventilation may increase the risk of pressure sores, tracheal tube dislocation or obstruction, drainage tube dislocation, and venous access removal (1,33). However, we found the risks associated with APP are extremely low in almost negligible numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The prone positioning (PP) is common respiratory support to improve oxygenation in acute respiratory distress syndrome (ARDS) in the intensive care unit (ICU) (1). Studies have demonstrated that those who benefit more from the PP are mechanically ventilated patients with moderate to severe ARDS and improved mortality (2).…”
Section: Introductionmentioning
confidence: 99%